Near‐infrared photoimmunotherapy (NIR‐PIT) on cholangiocarcinoma using a novel catheter device with light emitting diodes. Issue 2 (8th January 2021) - Hirata, Hajime; Kuwatani, Masaki; Nakajima, Kohei; Kodama, Yuki; Yoshikawa, Yasuo; Ogawa, Mikako; Sakamoto, Naoya
Abstract: Near‐infrared photoimmunotherapy (NIR‐PIT) is a novel therapy for cancers that uses NIR light and antibody‐photosensitizer (IR700) conjugates. However, it is difficult to deliver NIR light into the bile duct for cholangiocarcinoma (CCA) from the conventional extracorporeal apparatus. Thus, in this study, we developed a dedicated catheter with light emitting diodes (LEDs) that supersedes conventional external irradiation devices; we investigated the therapeutic effect of NIR‐PIT for CCA using the novel catheter. The new catheter was designed to be placed in the bile duct and a temperature sensor was attached to the tip of the catheter to avoid thermal burn. An anti‐epidermal growth factor receptor (EGFR) antibody, Panitumumab‐IR700 conjugate or anti‐human epidermal growth factor receptor type 2 (HER2) antibody, Trastuzumab‐IR700 conjugate, was used with EGFR‐ or HER2‐expressing cell lines, respectively. The in vitro efficacy of NIR‐PIT was confirmed in cultured cells; the capability of the new catheter for NIR‐PIT was then tested in a mouse tumor model. NIR‐PIT via the developed catheter treated CCA xenografts in mice. NIR‐PIT had an effect in Panitumumab‐IR700 conjugate‐ and Trastuzumab‐IR700 conjugate‐treated CCA cells that depended on the receptor expression level. Tumor growth was significantly suppressed in mice treated with NIR‐PIT using the novel catheter compared with controls ( P < .01). NIR‐PIT was an effective treatment for EGFR‐ and HER2‐expressing CCA cells, and the novel catheter with mounted LEDs was useful for NIR‐PIT of CCA. Abstract : A new catheter with light emitting diodes for photoimmunotherapy for cholangiocarcinoma was developed. The new catheter was designed to be placed in the bile duct and a temperature sensor was attached to the tip of the catheter to avoid thermal burn. Tumor growth was significantly suppressed in mice treated with NIR‐PIT using the novel catheter.